Early Bengali serials 1818-1950 a shared database of library holdings worldwide - Mukhopadhyay Asoknath (Kolkata K P Bagchi, 2004)
Early Bengali Serials (EBS) is a print version of the electronic database of an International Union Catalogue. The database includes over one thousand journals and newspapers that appeared during the period 1818 - 1950. Each title, with a few exceptions
Keywords: Bengali language; Serials; Union catalogues